2023
DOI: 10.3389/fped.2023.1121406
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for length of NICU stay of newborns: A systematic review

Abstract: BackgroundThe improvement in survival of preterm infants is accompanied by an increase in neonatal intensive care unit (NICU) admissions. Prolonged length of stay in the NICU (LOS-NICU) increases the incidence of neonatal complications and even mortality and places a significant economic burden on families and strain on healthcare systems. This review aims to identify risk factors influencing LOS-NICU of newborns and to provide a basis for interventions to shorten LOS-NICU and avoid prolonged LOS-NICU.MethodsA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 58 publications
1
2
0
1
Order By: Relevance
“…The LOS of very preterm infants < 28 weeks of gestation at birth was also 1.1–1.2 times longer than that of infants ≥ 28 weeks of gestation at birth. This result conforms with a recent systematic review not limited to infants with BPD; GA and/or birth weight have also been identified as critical risk factors affecting the initial LOS [ 29 ]. The earlier the GA at birth, the more days are expected for maturation until the term-equivalent age; therefore, the LOS will become longer.…”
Section: Discussionsupporting
confidence: 90%
“…The LOS of very preterm infants < 28 weeks of gestation at birth was also 1.1–1.2 times longer than that of infants ≥ 28 weeks of gestation at birth. This result conforms with a recent systematic review not limited to infants with BPD; GA and/or birth weight have also been identified as critical risk factors affecting the initial LOS [ 29 ]. The earlier the GA at birth, the more days are expected for maturation until the term-equivalent age; therefore, the LOS will become longer.…”
Section: Discussionsupporting
confidence: 90%
“…A systematic review from the year 2023 assessed 23 studies published with data from eleven countries, among these South Africa (1), Canada (1), China (4), United States of America (8), Eritrea (1), Ethiopia (1), India (2), Iran (1), Israel (1), Poland (1) and Turkey (2) and identified the gestational age, among other risk factors for higher stay of preterm newborns in NICUs, which are: birth weight, sepsis, necrotizing enterocolitis, bronchopulmonary dysplasia and retinopathy of prematurity; and reassured the need for further studies that investigate factors that affect the duration of hospitalization of PTNBs. 26 The challenge to this risk factors may represent an improvement in the survival of preterm newborns, with impacts in the reduction of length of hospitalization, and consequently public costs with health focused on this segment of the population.…”
Section: Discussionmentioning
confidence: 99%
“…Lebih tinggi dibandingkan dengan bayi yang lahir dengan usia kehamilan diatas 28 minggu, yakni mencapai 66-86 hari (Derienzo et al, 2016). Beberapa kondisi lain yang memengaruhi LOS NICU adalah perawatan antenatal ibu, kondisi ibu, penyakit dan kondisi bayi baru lahir, terapi yang diberikan, skor klinis dan hasil laboratorium (Fu et al, 2023).…”
Section: Pembahasanunclassified